FRI0569 SERUM AMYLOID A: ASSESSMENT OF REFERENCE VALUE AND COMPARISON OF SERUM CONCENTRATION IN HEALTHY SUBJECTS AND PATIENTS WITH BEHÇET SYNDROME. (13th June 2020) - Carbone, T.; Padula, M. C.; Pafundi, V.; Schievano, C.; Lascaro, N.; Padula, A.; Leccese, P.; D'angelo, S.
Abstract : Background: Serum amyloid A (SAA) is a family of acute-phase reactants. The rise of SAA concentration in blood circulation is a clinical marker of active inflammation in several auto-inflammatory diseases, including Behçet syndrome (BS). Despite its practical and analytical advantages, SAA measurement by ELISA has been mainly used as a research tool rather than for the routine laboratory testing due to the lack of a robust reference data in the literature. Objectives: Using the recommended procedures of the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC), we aimed to develop the SAA reference interval for a well-defined Italian healthy population (HC). Secondly, we compared the SAA serum concentration between HC and patients with BS. Methods: Sera specimens were collected from adult healthy blood donors after rule out the exclusion criteria (inflammatory disorders, ongoing infections, pregnancy and breastfeeding, obesity, using oral contraceptives, use of any medication, or consumed of alcohol), and from unselected BS patients fulfilling the International Study Group (ISG) classification criteria. Serum SAA concentrations were detected and quantified with a commercial solid phase sandwich enzyme-linked immunosorbent assay (Human SAA ELISA kit, IBL International GmbH, Hamburg, Germany) used on automated analyzer (Immunomat, SERION Diagnostic, Alifax, Polverara (PD), Italy) according to the manufacturer's protocol. Statistical analysis and data normalization of HC SAA values were carried out to determine the reference cut off. In the second step of the study, HC and BS patients were stratified in two groups according to the cut-off value. Results: We recruited 141 HC (84 M and 57 F; mean age, 44.5±13.2 years) and 63 BS patients (39 M and 24 F mean age, 45.3±13.2 years) assayed for SAA. The reference cut-off was calculated as 225 ng/ml. No statistically significant differences were found between males and females when SAA means were compared, suggesting that not gender-partitioned reference range is recommended for this analyte. After the stratification according to the cut-off value (group 1: < 225 ng/ml and group 2: > 225 ng/ml), we found 53/63 (84.1%) BS patients and 133/141 (94.3%) HC with concentration less than cut-off value, respectively. We identified 10/63 (15.9%) BS patients and 8/141 (5.7%) HC within the second group. The difference was statistically significant (p=0.0177; OR: 3.14, 95% CI: 1.17-3.38). Conclusion: This study allowed to define a widely accepted reference cut-off for the SAA detected by ELISA, responding to an unmet need of laboratory medicine. We found a statistically significant higher frequency of BS patients compared with HC when SAA values is higher than cut-off (225 ng/ml). This preliminary data could add significant information for better clarify the role of SAA as biomarker of inflammation and in guidance of clinical practice. Further studies will be required to stratify SAA values in relation to disease activity of BS. Disclosure of Interests: Teresa Carbone: None declared, Maria Carmela Padula: None declared, Vito Pafundi: None declared, Carlo Schievano: None declared, Nancy Lascaro: None declared, Angela Padula: None declared, Pietro Leccese: None declared, Salvatore D'Angelo Consultant of: AbbVie, Biogen, BMS, Celgene, Eli Lilly, MSD, Novartis, and UCB, Speakers bureau: AbbVie, BMS, Celgene, Eli Lilly, Novartis, Pfizer, and Sanofi